Experimental investigation on the physical, mechanical, and tribological behavior of brake friction composites for railway application - Sulaiman, Mohd Hafis; Leman, Zulkiflle; Mohamed Yusoff, Mohd Zuhri; Zainudin, Edi Syams; Budati, Sindhu (Malaysian Tribology Society (Mytribos), 2024)
Non asbestos brake friction composites with hemp fibre and rice husk (RH) reinforcements (20 weight %) were developed and characterized for physical, mechanical and tribological properties. The properties such as density, porosity, hardness (ASTM D785-03 standard HRR scale), impact strength, and wear rate (block-on-ring test ASTM G77 standard) were measured and compared with commercial brake block material sample. The experiment results showed that the hemp fibre-based composite has higher density (1.407 g/cm3), specific wear rate (0.164×10-2 mm3/Nm) and impact strength values than the RH reinforced composites. RH has higher impact strength (6 KJ/m2) and hardness (93.06 HRR) than the commercial brake block and hemp composite materials. From the evaluated results it can be concluded that Hemp reinforced phenolic composites can be used as alternative for existing brake materials. Dino lite digital microscope was used to examine the wear mechanism of the worn surfaces.